TAXPAYER COMPLIANCE IN PAYING RURAL AND URBAN LAND AND BUILDING TAXES (PBB-P2): A STUDY IN PASURUAN DISTRICT - Nurasik, Nurasik; Ningdiyah , Endra Wahyu; Abidin, Fitiyan Izzah Noor (PT. Antis International Publisher, 2024)
This research aims to analyze the influence of taxpayer awareness attitudes, tax service quality, tax rates and household income on taxpayer compliance in paying rural and urban land and building taxes (PBB-P2) in Pasuruan Regency . This research method uses quantitative research with primary data as a data source. The population of this research is all taxpayers in Pasuruan Regency, totaling 17,345 taxpayers . The sampling method used is Purposive Sampling . Because researchers use their own judgment by deliberately selecting members of the population who are deemed to be able to provide information, the selected respondents must meet the sample requirements, namely: every person or taxpayer who has a NPWP. The number of samples used in this research was 240 people. This research use analysis techniques regression linear multiple with data processing tools SPSS version 27 . The results of this research indicate that the Taxpayer's Awareness Attitude Influences Taxpayer Compliance. The Quality of Fisfus Services Influences Taxpayer Compliance. Tax Rates Affect Taxpayer Compliance. Household Income Influences Taxpayer Compliance